The influence of hepatic steatosis on the success of antiviral therapy for chronic hepatitis C - Preveden, Tomislav; Ružić, Maja; Pete, Maria K (Vojnosanitetski pregled, 2017)
Background/Aim. Chronic hepatitis C and liver steatosis often appear simultaneously in the same person, and steatosis can lead to worsening of liver disease and reducing the success of the treatment of chronic hepatitis C. Treatment of one disease can influence and cause favorable impact on treatment of other diseases. The aim of this study was to determine the incidence of liver steatosis in patients with chronic hepatitis C and to examine the impact of steatosis of the liver and other predictors on the success of antiviral therapy for chronic hepatitis C. Methods. The study included 123 patients with chronic hepatitis C treated with pegylated interferon alfa 2a in combination with ribavirin. The patients were divided into two groups based on the presence of cirrhosis: the group I consisted of 43 (34.9%) patients with steatosis and the group II consisted of 80 (65.1%) patients without liver steatosis. The success of the treatment was evaluated on the basis of the stable virological response. Results. The presence of steatosis was determined in 34.96% of the patients. The overall success of antiviral therapy was found in 74.79% of the patients. The success of antiviral therapy was present in 62.79% of the patients with hepatic steatosis, and in 81.25% the patients without steatosis (p < 0.05). The success of antiviral treatments was seen in 80.95% of the patients with hepatic steatosis and the genotype of hepatitis C virus 3. The predictors of antiviral therapy success for chronic hepatitis C in our study were patient's age, duration of infection, genotype 3, steatosis and severe fibrosis or cirrhosis. Conclusion. Liver steatosis is often present in patients with chronic hepatitis C. It has negative impact on the efficacy of antiviral therapy in patients with infection with genotype non-3 hepatitis C virus. Therefore, hepatic steatosis in these patients must be eliminated or treated prior to application of antiviral therapy.
Keywords: hepatitis c; fatty liver; genotype; age factors; interferon-alpha; ribavirin; treatment outcome